Spirometric and anthropometric improvements in response to elexacaftor/tezacaftor/ivacaftor depending on age and lung disease severity - Schütz, Katharina; Pallenberg, Sophia Theres; Kontsendorn, Julia; DeLuca, David; Sukdolak, Cinja; Minso, Rebecca; Büttner, Tina; Wetzke, Martin; Dopfer, Christian; Sauer-Heilborn, Annette; Ringshausen, Felix C.; Junge, Sibylle; et al. (Frontiers in Pharmacology, 2023)
Introduction: Triple-combination cystic fibrosis transmembrane conductance regulator (CFTR) modulator therapy with elexacaftor/tezacaftor/ivacaftor (ETI) was introduced in August 2020 in Germany for people with CF (pwCF) ≥12 years (yrs.) of age and in June 2021 for pwCF ≥6 yrs of age. In this single-center study, we analyzed longitudinal data on the percent-predicted forced expiratory volume (ppFEV1) and body-mass-index (BMI) for 12 months (mo.) after initiation of ETI by linear mixed models and regression analyses to identify age- and severity-dependent determinants of response to ETI. Methods: We obtained data on 42 children ≥6–11 yrs, 41 adolescents ≥12–17 yrs, and 143 adults by spirometry and anthropometry prior to ETI, and 3 and 12 mo. after ETI initiation. Data were stratified by the age group and further sub-divided into age-specific ppFEV1 impairment. To achieve this, the age strata were divided into three groups, each according to their baseline ppFEV1: lowest 25%, middle 50%, and top 25% of ppFEV1. Results: Adolescents and children with more severe lung disease prior to ETI (within the lowest 25% of age-specific ppFEV1) showed higher improvements in lung function than adults in this severity group (+18.5 vs. +7.5; p = 0.002 after 3 mo. and +13.8 vs. +7.2; p = 0.012 after 12 mo. of ETI therapy for ≥12–17 years and +19.8 vs. +7.5; p = 0.007 after 3 mo. for children ≥6–11 yrs). In all age groups, participants with more severe lung disease showed higher BMI gains than those with medium or good lung function (within the middle 50% or top 25% of age-specific ppFEV1). Regression analyses identified age as a predictive factor for FEV1 increase at 3 mo. after ETI initiation, and age and ppFEV1 at ETI initiation as predictive factors for FEV1 increase 12 mo. after ETI initiation. Discussion: We report initial data, which suggest that clinical response toward ETI depends on age and lung disease severity prior to ETI initiation, which argue for early initiation of ETI.